Resource rents and democratization in Sub-Saharan Africa - Ndlovu, Xichavo Alecia (My University, 2012)
The “political resource curse” hypothesis holds that countries rich in natural resources are less likely to democratize. This research report seeks to determine whether such a curse has afflicted sub-Saharan Africa during the two decades since the end of the Cold War. The possibility that abundant resources harm prospects for democratization is particularly worrying for Africa because the region is rich in minerals and oil and has had difficulty consolidating democratic institutions. Moreover, the region’s resource dependence is unlikely to decline in the midst of the ongoing boom in international commodity markets. To assess the “political resource curse” hypothesis, I use a combination of cross-national statistical analysis and nested case studies. In the statistical analysis, I determine whether African countries rich in natural resources in 1990 have been any less likely to have democratized by 2009 – controlling for potentially confounding factors like prior regime type, economic development, and ethnic fractionalization. I also use the statistical analysis to identify two resource-rich countries that experienced different political trajectories – Guinea and Zambia – and then present “nested” cases of trends in resource rents and political reform within them. My central finding is that little evidence exists to support the “political resource curse” hypothesis. Resource abundance is a poor statistical predictor of democratization : the negative association in the cross-national data is weak and statistically insignificant, and it disappears entirely if Africa’s five major oil-exporting countries are removed from the sample. Meanwhile, the dynamics in the case studies do not reveal any consistent link between trends in resource rents and political reform. If a “political resource curse” exists at all, it is most likely confined to major oil-exporting countries.
M.A. University of the Witwatersrand, Faculty of Humanities (International Relations), 2012